Determination of organochlorine pesticides and polychlorinated biphenyls residues in municipal solid waste compost by gas chromatography with electron-capture detection - Lourencetti, C.; Navickiene, S.; Ribeiro, M. L.; Santiaqo-Silva, M. (Vieweg, 2004)
A simple and efficient method for the simultaneous gas chromatographic determination of ten organochlorine pesticides (alpha-HCH, beta-HCH, gamma-HCH, p,p'-DDT, o,p'-DDT, p,p'-DDD, p,p'-DDE, aldrin, endrin, and dieldrin) and six congeners of PCBs (PCB 28, 52, 118, 138, 153, and 180) in municipal solid waste compost is described. The procedure involves a solid-phase dispersion matrix using celite as dispersant sorbent, alumina as clean up sorbent and hexane-dichloromethane (7:3, v/v) mixture as eluting solvent. An additional purification step with copper was necessary to eliminate sulphur. Analysis of the sample was performed by GC-ECD. The method was validated with fortified samples at two concentration levels (0.025 and 0.05 mg kg(-1)). Average recovery ranged from 77 to 121% with relative standard deviation between 1 and 18%. The detection limits, which ranged from 0.003 to 0.01 mg kg-1, were lower than those established by the Baden-Wurttemberg directive (0.033 mg kg(-1)).
Keywords: gas chromatography; electron capture detector; organochlorine pesticides and polychlorinated biphenyls; persistent organic pollutants; municipal solid waste